The international diffusion of pay for performance schemes in health system reform: Effectiveness of the approach or a paradigm shift in the making of health policy? - (:unkn) unknown (My University, 2018)
Explanation of the quasi-systematic emergence of performance-based financing in Africa, taking the example of Cameroon and Benin. Deconstruction of the existing theory that relies on the idea of performance to justify the almost unanimous adoption of this public policy in Africa. Two hypotheses: (1) the first is that the adoption of performance-based financing can hardly be explained by the notion of performance insofar as it is based on the achievement of results which remain mixed, and which do not concern the fundamentals of the health system; (2) the second hypothesis would be to explain the almost unanimous adoption of this public policy by the concept of political and cognitive convergence borrowed from the analysis of public policies, which highlights on the one hand an institutional context and on the other hand interactions between international and national actors which make it possible to understand the engineering of public development policies at work in African countries in particular, and in the South in general.
Keywords: African Research